Craniocervical Junction Visualization and Radiation Dose Consideration Utilizing Cone Beam Computed Tomography for Upper Cervical Chiropractic Clinical Application a Literature Review - Greg DeNunzio; Tyler Evans; Mychal E Beebe; Jaime Browning; Juha Koivisto (SAGE Publishing, 2022)
Objectives To highlight the detail obtained on a Cone Beam Computed Tomography (CBCT) scan of the craniocervical junction and its usefulness to Chiropractors who specialize in the upper cervical spine. A review of the dose considerations to patients vs radiography in a chiropractic clinical setting and to review the effective radiation dose to the patient. Methods A review of studies discussing cervical biomechanics, neurovascular structures, and abnormal radiographic findings, was discussed in relation to chiropractic clinical relevance. Further studies were evaluated demonstrating radiation dose to the patient from radiographs compared to CBCT. Results Incidental and abnormal findings of the craniocervical junction were shown to have superior visualization with CBCT compared to radiography. The radiation dose to the patient for similar imaging protocols to the craniocervical junction and cervical spine was equal or less utilizing CBCT when compared to radiographs. Conclusions The use of CBCT for visualization of the craniocervical junction and cervical spine in the chiropractic clinical setting allows for adjunctive visualization of the osseous structures which is germane to clinical protocol. Further with CBCT the effective dose to the patient is equal or less than similar imaging protocols utilizing radiographs to evaluate the craniocervical junction.